IMPLEMENTASI PROKER KKN DALAM MEMBANGUN NILAI SOSIAL DAN KEAGAMAAN DESA AIR PERIUKAN - Arzi, Muhammad Sidiq; Fahmi, Agung; Faraghita, Vania Salsabila; Oktasari, Nurwulan; Effendi, Sutrian (CV. Kalimasada Group, 2024)
This study examines the implementation of Community Service Program (KKN) in fostering social and religious values in Air Periukan Village. The KKN program, which involves students engaging with local communities, aims to enhance social cohesion and promote religious awareness among villagers. Through various activities such as workshops, community gatherings, and educational sessions, the program seeks to instill values that strengthen community bonds and encourage adherence to religious teachings. The research employs qualitative methods, including interviews and observations, to assess the impact of these initiatives on the villagers' social interactions and religious practices. Findings indicate that the KKN program has significantly contributed to the development of social solidarity and a deeper understanding of religious values, ultimately leading to a more cohesive and harmonious community. This study highlights the importance of integrating social and religious values in community development efforts, suggesting that such programs can serve as effective tools for fostering a sense of belonging and shared purpose within rural communities.